A Review on the Unsustainable Operations of Major Fast-Food Chains in the Philippines (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Fast-food chains hold massive market shares in the Philippines, and they actively respond to the massive demand for cheap and easy to acquire food. Nonetheless, they also pose various problems due to poor working standards and promote unhealthy eating habits. Their operations also involve unsustainable practices related to plastic usage and waste disposal that have contributed to the environmental degradation in the country. Hence, this study aims to analyze how the unsustainable practices in the operations of major fast-food chains in the Philippines can be addressed. This includes identifying and understanding the short-, medium- and long-term implications of the unsustainable practice and its possible relationship to the operations management of fast-food establishments. To address the problems found in the mentioned food industry, the researchers recommend specific potential mitigatory solutions. To conduct this study, the researchers applied the mixed-method design that consists of content analysis, survey questionnaires, and interviews with experts. The descriptive method of research that illustrates and explains situations is also used. Moreover, the 30 participants with related backgrounds to the topic (e.g., fast-food chain consumers and experts in food services) are picked through the Random Sampling technique. To ensure the confidentiality of gathered responses and privacy of the respondents, the researchers employ various ethical considerations in conducting the study. In terms of the customer psyche, this research finds out that there is a correlation between the values and practices of fast-food restaurants concerning the preservation of the environment. Customers perceive an establishment that utilizes unsustainable practices such as single-use plastic straws as a profit-driven business. This happens because most consumers now are against such environmental-damaging habits. This is intertwined with the finding that there is a growing belief that businesses need to practice social responsibility, especially toward environmental concerns. Furthermore, this supports the direct correlation between the awareness of unsustainable practices of fast-food chain buyers and their consumption patterns. Additionally, unsustainable activities are strongly linked to the operational management of fast-food chain industries. This is primarily rooted in the market commodity nature of food, wherein food is exchanged on a commercial basis and free competition. Despite food being survival sustenance, food purchases are reduced to a customer footprint within a capitalistic market. Hence, the food market commodity nature and the competitive market of the food industry have resulted in unsustainable behaviors in all aspects of the food system. Nonetheless, the findings reveal that the company can implement specific practices to more sustainable practices. The researchers created various recommendations to ease the problems mentioned earlier, such as rewarding customers for bringing their own set of utensils, sourcing locally made products, and improving communication between consumers and co-workers. It is concluded that environmental awareness and sustainable practices are essential in the operations of the fast-food industry, and it can be achieved through various means.
Keywords: unsustainable practices; fast-food chains; operational management; sustainability; environment